There's a Word for That - Tanen, Sloane (New York, 2019)
The wildly flawed and dysfunctional Kessler family--retired film producer Marty; his daughter Janine, a former child star; granddaughter Hailey; and long-forgotten first wife, Bunny--comes together in Malibu's most exclusive rehab center.
Keywords: Families; Fiction; Rehabilitation centers; Fiction; Domestic fiction